2014
DOI: 10.1159/000367903
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Ultraviolet Light Exposure and Mortality in Dialysis Patients

Abstract: Background: Emerging data suggest that reduced exposure to ultraviolet (UV) radiation is associated with increased mortality in the general population. To date, the association between UV exposure and mortality in dialysis patients has not been examined. Methods: We examined the association between UV index, a proxy of UV exposure, and all-cause mortality among 47,286 US dialysis patients (entry period 2001-2006, with follow-up through 2009) from a large national dialysis organization using multivariable Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…119 There is a strong latitudinal gradient of increasing rates of hospital admission for anaphylaxis (a severe allergic reaction) in children in Chile; that is, with increasing latitude above 34°S and lower levels of solar UV radiation. 120 An inverse association between mortality from all causes and levels of UV radiation or personal sun exposure have been described for dialysis patients, 121 female participants of a large cohort study in Sweden at the 20-year follow-up, 122 and in premature babies (23-28 weeks gestation) in the first 28 days of life. 123 Many commonly used drugs can be phototoxic or cause photosensitivity.…”
Section: 7mentioning
confidence: 98%
“…119 There is a strong latitudinal gradient of increasing rates of hospital admission for anaphylaxis (a severe allergic reaction) in children in Chile; that is, with increasing latitude above 34°S and lower levels of solar UV radiation. 120 An inverse association between mortality from all causes and levels of UV radiation or personal sun exposure have been described for dialysis patients, 121 female participants of a large cohort study in Sweden at the 20-year follow-up, 122 and in premature babies (23-28 weeks gestation) in the first 28 days of life. 123 Many commonly used drugs can be phototoxic or cause photosensitivity.…”
Section: 7mentioning
confidence: 98%
“…We conducted an observational study using data from a large national dialysis organization in the United States with detailed patient-level information on sociodemographics, comorbidities, laboratory tests, and vital status (20,21). Our source population was a mixed incident and prevalent cohort of 7323 adult dialysis patients who solely received PD from one of the facilities operated by the dialysis provider over the period of January 1, 2007 to December 31, 2011.…”
Section: Source Cohortmentioning
confidence: 99%
“…In 2014, Shapiro et al . reported that among 47,286 US dialysis patients, those residing in higher ultraviolet (UV) index regions had lower all-cause mortality compared to those living in moderate-high UV regions 22 . The average of the annual noon-time UV index value was calculated in each patient during the follow-up periods.…”
Section: Discussionmentioning
confidence: 99%